Dual-band monopole antennas for RF energy harvesting from the environment - Edison Andres Zapata Ochoa (Universidad de las Fuerzas Armadas ESPE, 2022)
This paper presents two low-cost dual-band antennas for collecting ambient RF energy from the GSM-850, GSM-1900, and UMTS-2100 MHz bands. Both rectennas (Rectifying Antennas) are based on Defected Grounded Structure (DGS) antennas. The first one is designed with a square resonator ring. The bandwidth is between 73.4 and 145 MHz, with a gain of 2.29 and 3.53 dBi. The other one has a bandwidth of 86 and 124.8 MHz with a gain of 1 and 3.8 dBi. In addition, a triple-band rectifier with an HSMS-286C Schottky diode is used to improve the RF to DC power conversion efficiency. Measurement results show that between 150 and 308 mV of DC is harvested during 8 hours at 50 meters from a telephone base station, in a total of 86 continuous hours of exposure to this station, a DC voltage varying between 4.0 and 4.50 volts of ambient RF energy is obtained.